Acute Bacterial Meningitis and Systemic Abscesses due to Streptococcus dysgalactiae subsp. equisimilis Infection. (23rd April 2017) - Jourani, M.; Duprez, T.; Roelants, V.; Rodriguez-Villalobos, H.; Hantson, P.
Abstract : Disseminated abscesses due to group G β -hemolytic Streptococcus dysgalactiae were observed in a 57-year-old cirrhotic patient with the skin being the putative way of entry for the pathogen. S. dysgalactiae is a rare agent in human infections responsible for acute pyogenic meningitis. The mortality rate associated with S. dysgalactiae bacteraemia and meningitis may be as high as 50%, particularly in the presence of endocarditis or brain abscesses. In our patient, main sites of infections were meningitis and ventriculitis, spondylodiscitis, septic arthritis, and soft-tissue infections. In contrast, no endocarditis was evidenced. Cirrhosis-related immune suppression was considered as a pathophysiological cofactor for the condition. Fortunately, clinical status improved after long-term (3 months) antimicrobial therapy.